2018
DOI: 10.1080/02656736.2018.1476738
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pulmonary aspergillosis secondary to microwave ablation: a multicenter retrospective study

Abstract: Lung MWA may be an additional host risk factor for IPA, particularly in elderly patients with underlying diseases and in patients who have recently undergone chemotherapy. Early and accurate diagnosis of IPA after MWA is critical for patient prognosis. Voriconazole should be given as the first-line treatment as early as possible. Bronchial artery embolization or intracavitary lavage may be required in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
(46 reference statements)
1
7
0
Order By: Relevance
“…Pneumonia (4.5%) could be effectively cured by appropriate antibiotics as previously reported [19,35]. There was no reported case of life-threatening invasive aspergillosis [36,37]. Nerve injury of brachial plexus (1.5%) has been rarely reported and the symptoms partially receded over time [38].…”
Section: Discussionmentioning
confidence: 54%
“…Pneumonia (4.5%) could be effectively cured by appropriate antibiotics as previously reported [19,35]. There was no reported case of life-threatening invasive aspergillosis [36,37]. Nerve injury of brachial plexus (1.5%) has been rarely reported and the symptoms partially receded over time [38].…”
Section: Discussionmentioning
confidence: 54%
“…The incidence of pleural effusions requiring drainage in the current study is in accordance with that reported in previous studies, and the incidence of Aspergillus infection in the current study is consistent with that reported by Huang et al . (1.44%) …”
Section: Discussionmentioning
confidence: 98%
“…33 The incidence of pleural effusions requiring drainage in the current study is in accordance with that reported in previous studies, 20,33 and the incidence of Aspergillus infection in the current study is consistent with that reported by Huang et al (1.44%). 34 This study had several limitations: (i) it used a small sample size; (ii) it was retrospective in nature; (iii) data on factors that could influence outcomes were unavailable; and (iv) multiple devices were used by multiple operators.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of 1,596 patients, 23 developed an IA after microwave therapy. 86 The patients with IA were more likely to be male and to have COPD, history of smoking, and primary lung tumor.…”
Section: Solid Tumorsmentioning
confidence: 99%